The global dissemination of bacterial infections necessitates the study of reverse genomic epidemiology. (4th February 2019) - Ruan, Zhi; Yu, Yunsong; Feng, Ye
Abstract: Whole genome sequencing (WGS) has revolutionized the genotyping of bacterial pathogens and is expected to become the new gold standard for tracing the transmissions of bacterial infectious diseases for public health purposes. Traditional genomic epidemiology often uses WGS as a verification tool, namely, when a common source or epidemiological link is suspected, the collected isolates are sequenced for the determination of clonal relationships. However, increasingly frequent international travel and food transportation, and the associated potential for the cross-border transmission of bacterial pathogens, often lead to an absence of information on bacterial transmission routes. Here we introduce the concept of 'reverse genomic epidemiology', i.e. when isolates are inspected by genome comparisons to be sufficiently similar to one another, they are assumed to be a consequence of infection from a common source. Through BacWGSTdb (http://bacdb.org/BacWGSTdb /), a database we have developed for bacterial genome typing and source tracking, we have found that almost the entire analyzed 20 bacterial species exhibit the phenomenon of cross-border clonal dissemination. Five networks were further identified in which isolates sharing nearly identical genomes were collected from at least five different countries. Three of these have been documented as real infectious disease outbreaks, therefore demonstrating the feasibility and authority of reverse genomic epidemiology. Our survey and proposed strategy would be of potential value in establishing a global surveillance system for tracing bacterial transmissions and outbreaks; the related database and techniques require urgent standardization.